An urban household living wage: A conceptual overview - Cyreel Ovyenne Oneh; Siti Hajar Samsu (Faculty of Business, Economics and Accountancy, 2021)
As Malaysia steps closer to become a high-income nation, it is time for all citizens to aspire to at least a minimum acceptable standard of living. The rising cost of living poses difficulties for households to maintain an adequate standard of living. This study aims to investigate the living wage of household in Kota Kinabalu and to determine the factors that influence the living wage. In this context, a household refers to an individual or a group of individuals, whether related or not, who live together in the same house and make economic decisions together. The living wage calculation applied the Anker Formula, Ordinary Least Squares (OLS) are used to determine the relationship between the variables. For data collection, this study employs a quantitative approach strategy in which self-developed questionnaires are distributed to respondents around Kota Kinabalu. The pilot study results indicates that the total living wage needed for the household with different number of full-time workers is slightly different. The range of living wage for one full-time worker were between RM1400 to RM1600 monthly, RM1700 to RM1800 monthly for the two full-time worker household and RM1000 to RM1200 monthly for the three full-time worker household. Previous literature shows that housing cost, food cost, transportation cost, communication cost, healthcare cost, education cost, household size, number of full-time workers and savings are the factors that significantly influenced the living wage. On this basis, the authorities should emphasize more on these factors when setting the minimum wage policy particularly in the urban area such as Kota Kinabalu, Sabah.